KONSEP KEPALA MADRASAH SEBAGAI INSTRUCTIONAL LEADER - Kusumawati Kusumawati (Conciencia, 2015)
Headmaster of school / madrasah is central to education. Headmaster as a facilitator for the development of education as well as executing a task laden with hope and renewal. The role of headmaster of an educational leader is indispensable. Madrasah development and learning is progressing very significant, one cause may have been implementing the concept of instructional leader by the headmaster. Because of this, this paper aims to determine how the concept headmaster as instructional leader in improving the quality of learning. The school headmaster as instructional leader can achieve the goal of improving student learning and success in the first way, helping to divert attention from teaching to learning; second, creating a shared goal among teachers about the spirit of third student, using the data with the aim that the teacher is able to develop the education of students both as individuals and groups, fourth, providing support to teachers by providing training, instructional media and support needed to help students in achieve success. and fifth, align curriculum, instruction and assessment.